(untitled) (Journal of Interior Design and Academy, 2023)
Earthquakes are among the most deadly and destructive natural disasters. They have catastrophic consequences for human life. Every year, thousands of people worldwide are affected by earthquakes, struggling with psychological and physical damage. Educational buildings, which are especially used by students, are damaged by structural and non-structural elements during earthquakes, and individuals caught in the earthquake are injured and even lost their lives. Furniture, which is classified as non-structural elements, can reduce non-structural risks caused by earthquakes with measures to be taken. As a result of the study’s keyword search, a literature review was conducted by the use of different academic search engines. The fundamental interior spaces of educational buildings were defined with 7 different definitions. Literature sources found as a result of keyword analysis were used to define the furniture in the interior spaces and 7 fundamental pieces of furniture were defined. Accordingly, 6 different earthquake risk mitigation measures for furniture were analyzed and evaluated.